STRATEGI BRAND POSITIONING SEKKA CRAFT BALIGE: PELESTARIAN IDENTITAS LOKAL DI TENGAH TANTANGAN FAST FASHION DAN PENURUNAN DAYA BELI - Estiagusrini Simanjutak; Septrio Hamonangan; Hans Twin Immanuel Manik; Santi Agustina Manik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Sekka Craft Balige faces a decline in sales due to changes in consumer behavior after the pandemic and the rapid growth of fast fashion that offers cheaper and trend-driven products. This study aims to analyze the brand positioning strategy of Sekka Craft by focusing on the role of cultural identity based on Toba mandar cloth as the core element of its brand. The study uses a qualitative approach with thematic analysis to identify patterns that appear from interviews and field observations. The analysis shows three key findings. First, cultural identity becomes a strong differentiator because the product carries historical and symbolic meaning for the Toba community. Second, the decline in purchasing power and the dominance of fast fashion reduce perceived value, brand awareness, and customer visits. Third, the absence of updated positioning strategies weakens brand relevance in the modern market. The results show that Sekka Craft needs to strengthen cultural storytelling, improve product design, and build a stronger emotional connection with customers. The study provides insight into how cultural-based brand identity can become a competitive advantage for local craft businesses.